Performance of drip emitters for different pressures and application of cashew nuts wastewater (2018)
The effect of different operating pressures is investigated with regard to the clogging of drip emitters and Christiansen uniformity coefficient (CUC) in drip irrigation systems operating with wastewater from cashew nut processing. The experiment was set on a split-split-plot scheme, with operating pressures (70, 140, 210 and 280 kPa) on plots, emitter models (G1, G2 and G3) on split-plots and assessment times (0, 20, 40, 60, 80, 100, 120, 140 and 160 h) on split-split-plots, in a completely randomized design, with three replicates. CUC of irrigation units was measured every 20 h up to operation time of 160 h. Results showed that drip emitters G2 and G3 were the most suitable for the application of cashew nut wastewater, and the operating pressure of 140 kPa minimized clogging in drip emitters G1, G2 and G3 when operated with cashew nut wastewater.